Digital Economic Transformation Through E-Commerce and Fintech in Improving Smes Income - Wahyu Indah Sari; Annisa Sanny; Eli Delvi Yanti; Maharani Era (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The goal to be achieved from this service is the application of the digital economy through e-commerce and fintech for MSME actors in Kota Pari Village. Then it is hoped that the community/MSME actors will be able to understand that this digital economic transformation is used for the turnover of economic activities so that it will increase the income of business actors in the Pandemic Era so that the products offered are not only marketed in the local area but also internationally. Business actors are increasingly aware of this digital economic transformation, so it is hoped that they will be able to increase their income through product sales by increasing production, expanding sales areas in e-commerce that are already available on the android application. This service activity plan will be carried out for 1 day with counseling with the theme of Education on Digital Economy Transformation Through E-commerce and Fintech in increasing the income of business actors in the COVID-19 Pandemic Era in Kota Pari Village, Pantai Cermin District, Serdang Bedagai Regency and evaluating the results by re-observing the community/MSME actors by looking at the income results and the level of purchasing power of the community.